A Reflective Perspective of In-Depth Qualitative Inquiry on Teachers’ Preparation Policies and Execution for Vocational High School in Indonesia - Didik Nurhadi; Ming-Chang Wu (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2019)
This study investigates teachers' preparation policies and the policy execution in vocational high school in Indonesia. Using a qualitative method, the researcher selected university members who have been involved in teacher preparation programs and or policy making in Indonesia as the participants. The data collection and analysis were undertaken according to research questions focused on the governmental policies and the implementation of teachers' preparation. This result shows that teacher preparation policies in Indonesia were enacted based on the teacher and lecturer law in 2005. Afterward, in 2007, the minister of education upgraded a policy through two regulations, the teacher's qualification and competencies, and teacher certification. To get teacher certificate and incentives from the government, vocational high school teachers should make portfolios and join series of training. This, certainly, effectively encourages many youngsters to become a teacher. The policy of teacher certification was updated and upgraded again by the government through teacher education program through either in-service or pre-service. The teacher preparation policies are conducted by Indonesian government through teacher certification, that focuses on the quantity of certified teachers based on the national standard. Consequently, teachers will face difficulty in creating graduates with high competency standards and high competitiveness in the global market. Teacher quality improvement should be done clearly with the orientation on international standard.